2023
DOI: 10.1021/acs.iecr.2c04484
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Desulfurization of Benzothiophene by Persulfate and Cu-Loaded g-C3 N4 via the Polymerization Pathway

Abstract: Turning aromatic sulfur impurities to value-added polymers is a promising technology for fuel desulfurization. In this study, Cu(I,II)@g-C 3 N 4 plates prepared via facile calcination show high reactivity in catalytic oxidation of benzothiophene (BT) by persulfate in a mixture of MeCN/H 2 O (v/v = 50/50). Quenching experiments rule out the primary contributions of SO 4•− , • OH, and O 2•− to BT oxidation and confirm the presence of carbon-centered radicals during the desulfurization process. XPS and Raman anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, the slight shift of the (002) plane of Bi–Mo/CN-2 from 27.6 to 27.4° compared with those of CN, Bi/CN, and Mo/CN indicates the increased stacking distance between the CN nanosheets due to the addition of Bi and Mo in pyrolysis. Our recent work suggested that the doped Cu­(II) influenced the crystallinity of CN by bringing about a shift of the diffraction peak at 27.4 to 27.6° and the decreased peak intensities of the (002) plane . Moreover, the absence of Bi and/or Mo oxides in the XRD patterns of Bi/CN, Mo/CN, and Bi–Mo/CN-2 indicates the uniform distribution of Bi and/or Mo in the CN structure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, the slight shift of the (002) plane of Bi–Mo/CN-2 from 27.6 to 27.4° compared with those of CN, Bi/CN, and Mo/CN indicates the increased stacking distance between the CN nanosheets due to the addition of Bi and Mo in pyrolysis. Our recent work suggested that the doped Cu­(II) influenced the crystallinity of CN by bringing about a shift of the diffraction peak at 27.4 to 27.6° and the decreased peak intensities of the (002) plane . Moreover, the absence of Bi and/or Mo oxides in the XRD patterns of Bi/CN, Mo/CN, and Bi–Mo/CN-2 indicates the uniform distribution of Bi and/or Mo in the CN structure.…”
Section: Resultsmentioning
confidence: 98%
“…The oxidizing species on the surface of catalysts (e.g., superoxo and peroxo species) can effectively mediate the oxidation selectivity of H-rich substrates via the H-abstraction pathway. , For instance, our recent works suggested that the surface Bi–OO• superoxo and Bi–OOH peroxo during the photocatalytic activation of O 2 on Bi 2.15 WO 6 not only selectively oxidized benzyl alcohol to benzaldehyde via the H-abstraction pathway, but also contributed to the oxidation of various H-donors such as As­(III), glucose and phenolics with the production of H 2 O 2 , indicating the high reactivity of surface superoxo and peroxo species in H-abstraction . Likewise, Lyu et al suggested that the surface Ti–OOH peroxo on Pd@HTS-1 achieved 46.4% conversion of benzyl alcohol with high selectivity of 100% toward benzaldehyde.…”
Section: Introductionmentioning
confidence: 99%